The pathological potential of ependymal cells in mild traumatic brain injury - Nelles, Diana G.; Hazrati, Lili-Naz (Frontiers in Cellular Neuroscience, 2023)
Mild traumatic brain injury (mTBI) is a common neurological condition affecting millions of individuals worldwide. Although the pathology of mTBI is not fully understood, ependymal cells present a promising approach for studying the pathogenesis of mTBI. Previous studies have revealed that DNA damage in the form of γH2AX accumulates in ependymal cells following mTBI, with evidence of widespread cellular senescence in the brain. Ependymal ciliary dysfunction has also been observed, leading to altered cerebrospinal fluid homeostasis. Even though ependymal cells have not been extensively studied in the context of mTBI, these observations reflect the pathological potential of ependymal cells that may underlie the neuropathological and clinical presentations of mTBI. This mini review explores the molecular and structural alterations that have been reported in ependymal cells following mTBI, as well as the potential pathological mechanisms mediated by ependymal cells that may contribute to overall dysfunction of the brain post-mTBI. Specifically, we address the topics of DNA damage-induced cellular senescence, dysregulation of cerebrospinal fluid homeostasis, and the consequences of impaired ependymal cell barriers. Moreover, we highlight potential ependymal cell-based therapies for the treatment of mTBI, with a focus on neurogenesis, ependymal cell repair, and modulation of senescence signaling pathways. Further insight and research in this field will help to establish the role of ependymal cells in the pathogenesis of mTBI and may lead to improved treatments that leverage ependymal cells to target the origins of mTBI pathology.